EFFECTIVENESS OF ISCHEMIC COMPRESSION ON TRAPEZIUS MYOFASCIAL TRIGGER POINTS IN NECK PAIN (International Journal of Physiotherapy, 2016)
Background: Neck pain is a common disorder prevailing among individuals of different populations. The myofascial pain syndrome is a disorder related to myofascial trigger points. It is defined as a hyperirritable locus in skeletal muscle and that is associated with a hypersensitive palpable nodule in a taut band of muscle. Manual therapy has got a profound role in treating and ischemic compression technique has been researched widely. Thus the study intends to analyse the effectiveness of Manual Therapy (Ischemic Compression) on functional outcome in neck pain.Methods: A single blinded randomized control study was conducted for subjects of sample size 30 who met the inclusion criteria and random allocation was made. The baseline parameters as like pain severity using VAS, pain pressure threshold using pressure Algometer, active cervical lateral flexion using 360 degree goniometer and disability using NDI were recorded. Study group received ischemic compression followed by myofascial stretches while the control group received ultrasonic therapy of 1.4watts/cm2. Both received Cryotherapy post session. After 2 weeks the baseline parameters were again recorded for t-test analysis.Result: There was no statistical significance between groups (p≥0.05). But active cervical lateral flexion showed improved mobility in study group and a high statistical significance within groups (p≤0.01) in relation to all parameters.Conclusion: Both ultrasonic therapy and Ischemic compression technique was found to show better improvement inpain pressure threshold and functional outcome in neck pain.